Micro-Sized glucose biosensor based on composite pH sensor - Bal Altuntas, Derya; Tavukcuoglu, Ozlem (PAMUKKALE UNIV, 2018)
Today's scientific and technical advances have led to significant advances in biosensor technology, leading to widespread use of biosensors in areas such as food technology, the environment, pharmaceuticals and clinical diagnostics, biochemistry, and analytical chemistry. Improvements in the ion-selective sensor technology used in the preparation of potentiometric biosensors and the increase in the number of sensor materials have also accelerated the development of new types of potentiometric biosensors. Thus, in this study, information is given on the development of a new micro sized potentiometric glucose biosensor based on composite pH sensor. Glucose oxidase was immobilized on the composite layer as the biorecognition element. The surface of glucose biosensor based composite pH sensing matrices was first examined for electrochemical elucidation by using cyclic voltammetry and electrochemical impedance spectroscopy. The rate of electron transfer resulted in a stable response behavior of the biosensor and made it a suitable potentiometric sensor for detection of glucose. A linear response in concentration range from 5x10(-5) to 1x10(-1) mol/L was obtained with a detection limit of 2x10(-5) mol/L for the potentiometric detection of glucose. The biosensor exhibited a fast response time (10 s), had good stability, and an extended lifetime.
Keywords: Solid-state composite sensor; Miniatruization; Diabet follow-up; Glucose biosensor; CRITICALLY-ILL; POLYMERS; Engineering